The direct drivers of ethnocentric consumer, intention and actual purchasing behavior in Malaysia - Nik Mat, Nik Kamariah (World Academy of Science, Engineering and Technology, 2015)
The Malaysian government had consistently revived its campaign for “Buy Malaysian Goods” from time to time.The purpose of the campaign is to remind consumers to be ethnocentric and patriotic when purchasing product and services.This is necessary to ensure high demand for local products and services compared to foreign products.However, the decline of domestic investment in 2012 has triggered concern for the Malaysian economy. Hence, this study attempts to determine the drivers of actual purchasing behavior, intention to purchase domestic products and ethnocentrism. The study employs the cross-sectional primary data, self-administered on household, selected using stratified random sampling in four Malaysian regions.A nine factor driver of actual domestic purchasing behavior (culture openness, conservatism, collectivism, patriotism, control belief, interest in foreign travel, attitude, ethnocentrism and intention) were measured utilizing 60 items, using 7-point Likertscale. From 1000 questionnaires distributed, a sample of 486 were returned representing 48.6 percent response rate. From the fit generated structural model (SEM analysis), it was found that the drivers of actual purchase behavior are collectivism, cultural openness and patriotism; the drivers of intention to purchase domestic product are attitude, control belief, collectivism and conservatism; and drivers of ethnocentrism are cultural openness, control belief, foreign travel and patriotism.It also shows that Malaysian consumers scored high in ethnocentrism and patriotism.The findings are discussed in the perspective of its implication to Malaysian National Agenda.